Novel candidate genes for cholesteatoma in chronic otitis media - Lee, Nam K.; Cass, Stephen P.; Gubbels, Samuel P.; Gomez, Helen Z.; Scholes, Melissa A.; Jenkins, Herman A.; Santos-Cortez, Regie Lyn P. (Frontiers in Genetics, 2023)
Cholesteatoma is a rare and benign disease, but its propensity to cause erosive damage through uninhibited growth can be detrimental to hearing and health. Prior reports indicated a genetic component to pathogenesis in at least a subset of patients. In this study, we aimed to identify rare DNA variants in affected patients. The salivary DNA of six patients whose middle ear tissues were obtained during tympanoplasty/mastoidectomy surgeries were submitted for exome sequencing. Tissue samples from the same patients were previously submitted for mRNA sequencing and analyzed for differentially expressed genes (DEGs). From the generated exome sequence data, rare predicted-to-be-damaging variants were selected within previously identified DEGs, and the candidate genes within which these rare variants lie were used for network analysis. Exome sequencing of six DNA samples yielded 5,078 rare variants with minor allele frequency <0.001. A total of 510 variants were predicted to be deleterious and 52 were found to lie within previously identified DEGs. After selecting variants based on quality control measures, 12 variants were identified all from one pediatric patient. Network analysis identified ten significant cellular pathways, including protein transport, viral process, regulation of catalytic activity and cell cycle, and apoptotic and rhythmic processes. We hypothesize that the candidate genes identified in this study may be part of key signaling pathways during the mucosal response to middle ear infection. The occurrence of multiple rare variants may play a role in earlier onset of cholesteatoma formation in chronic otitis media.